Race in a godless world : atheism, race, and civilization, 1850-1914 - Alexander, Nathan G. (Manchester University Press, 2019)
This is the first historical analysis of the racial views of atheists and freethinkers. Focusing on Britain and the United States in the second half of the nineteenth century, it covers racial and evolutionary science, imperialism, slavery and segregation in the United States, immigration debates and racial prejudice in theory and practice.